1987
DOI: 10.1161/01.cir.75.3.611
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of myocardial injury produced by temporary coronary artery occlusion and reflow with technetium-99m-pyrophosphate.

Abstract: Previously, technetium-99m-stannous pyrophosphate (99mTc-PPi) has been used to localize and estimate the size of myocardial infarcts in animals after permanent coronary artery occlusion. This study tested the hypothesis that 99mTc-PPi accurately sizes myocardial infarctions produced by temporary coronary artery occlusion and reflow in dogs. Three groups of dogs were studied: group A underwent 3 hr of occlusion followed by 2 hr of reperfusion, with 99mTc-PPi injected 10 min after reflow (n = 10); group B underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…These authors hypothesized that in clinical imaging, and depending on the threshold level required for tracer detection, there could be a very marked discrepancy between scintigraphic estimates of infarct size with 99mTc PYP and "'In Ab, particularly in reperfused infarcts. This is supported by the data of Jan sen et al [12] who demonstrated that scintigraphic infarct size with 99mTc PYP is significantly larger when 99mTc PYP is injected after 3 h of reperfusion rather than after 48 h of reperfusion, following a 3-hour coronary occlu sion. This observation is consistent with 99mTc uptake in injured but viable myocytes.…”
Section: Mtc Pyrophosphatesupporting
confidence: 64%
“…These authors hypothesized that in clinical imaging, and depending on the threshold level required for tracer detection, there could be a very marked discrepancy between scintigraphic estimates of infarct size with 99mTc PYP and "'In Ab, particularly in reperfused infarcts. This is supported by the data of Jan sen et al [12] who demonstrated that scintigraphic infarct size with 99mTc PYP is significantly larger when 99mTc PYP is injected after 3 h of reperfusion rather than after 48 h of reperfusion, following a 3-hour coronary occlu sion. This observation is consistent with 99mTc uptake in injured but viable myocytes.…”
Section: Mtc Pyrophosphatesupporting
confidence: 64%
“…The use of infarct size as a surrogate outcome in phase II clinical trials as a preliminary estimate of treatment effect is predicated on the previously demonstrated relationship between CK-MB and infarct size [4,5,7,8], and between infarct size and meaningful clinical outcomes [8-22]. Thus, it is important to define the most accurate and reliable method to estimate infarct size using CK-MB measures as surrogate endpoints in clinical trials of treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between creatine kinase (CK)-MB measured in the blood and infarct size has been well-established through both pathological and imaging correlations [1-8]. Furthermore, infarct size, measured by release of CK-MB for example, is associated with short- and long-term cardiovascular complications such as cardiac death, reinfarction, congestive heart failure, stroke and unstable angina requiring hospitalization [9-19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have described an overestimation of infarct size calculated by Tc-99m PYP in preparations of temporary coronary occlusions followed by reperfusion, but Jansen reported that SPECT imaging with adequate threshold makes possible accurate localization and determination of infarct size when Tc-99m PYP was injected 90 min or more after reflow. 12 So SPECT with Tc-99m PYP is attractive for the evaluation of acute infarct size.…”
Section: Discussionmentioning
confidence: 99%